Study of the influence of the vitamin-mineral complex "Silicon active" on the condition of the periodontal tissues of rats during the modeling of periodontitis - S. A. Schnaider; M. V. Anisimov; A. V. Maslov; E. K. Tkachenko (Journal of Education, Health and Sport, 2017)
The purpose of the research was to study the effects of the vitamin-mineral complex "Silicon Active" on the condition of periodontal tissues of rats under the conditions of modeling periodontitis with the help of exogenous hyaluronidase.